Kejadian Indel Simultan pada Intron 7 Gen Branched-Chain α-Ketoacid Dehydrogenase E1a (BCKDHA) pada Sapi Madura - Asri Febriana; Achmad Farajallah; Dyah Perwitasari (Jurnal Ilmu Pertanian Indonesia, 2015)
Madura cattle is one of the Indonesian local cattle breeds derived from crossing between Zebu cattle (Bos indicus) and banteng (Bos javanicus). Branched-chain α-ketoacid dehydrogenase (BCKDH) is one of the main enzyme complexes in the inner mitochondrial membrane that metabolizes branched chain amino acid (BCAA), ie valine, leucine, and isoleucine. The diversity of the nucleotide sequences of the genes largely determine the efficiency of enzyme encoded. This paper aimed to determine the nucleotide variation contained in section  intron 7, exon 8, and intron 8 genes BCKDHA on Madura cattle. This study was conducted on three Madura cattle that used as bull race (karapan), beauty contest (sonok), and beef cattle. The analysis showed that the variation in intron higher than occurred in the exon. Simultaneous indel found at base position 34 and 68 in sonok cattle. In addition, the C266T variant found in beef cattle. These variants do not cause significant changes in amino acids. There was no specific mutation in intron 7, exon 8, and intron 8 were found in Madura cattle designation. This indicated the absence of differentiation Madura cattle designation of selection pressure of BCKDHA gene.